Forgiveness Psychoeducation with Emerging Adults: REACH Forgiveness and Community Campaigns for Forgiveness - Everett L. Worthington (MDPI AG, 2024)
Much attention has been devoted to the effectiveness of forgiveness interventions in children and adolescents featuring two premier programs by Enright and his colleagues. Little attention has been given to psychoeducational forgiveness interventions with emerging adults. This is a narrative review of REACH Forgiveness studies with emerging adults (ages 18-25). The life tasks of emerging adults justify offering psychoeducational interventions to emerging adults. Research studies on REACH Forgiveness (k = 17), non-REACH Forgiveness studies (k = 4), and community campaigns at universities (k = 4) with emerging adults are summarized. Effect sizes per hour (d/h) for REACH Forgiveness studies (k = 13 for psychoeducational groups; k = 4 for self-administered workbooks) are reported. The proto-REACH groups (k = 5) had mean d/h = 0.104; REACH groups (k = 9) had d/h = 0.101; self-administered workbooks (k = 3) had mean d/h = 0.15; non-REACH Forgiveness studies (k = 4) had d/h = 0.09. All studies were from the USA, and most were from universities. However, a recent article reported randomized controlled trials in five non-USA samples of adults (N = 4598). A 3.34-h workbook had d/h = 0.16, suggesting that the workbook might be effective with emerging adults around the world. Finally, three USA Christian universities had public health immersion campaigns to promote forgiveness, and a community psychoeducational campaign in 2878 secular university students in Colombia (of ~9000 total) allowed choices among 16 psychoeducational activities. The number of activities used was proportional to forgiveness experienced. For forgiveness, d = 0.36 plus substantial reductions in depression and anxiety, indicating strong public health potential of forgiveness psychoeducation in emerging adults worldwide.